PERTUMBUHAN DAN PRODUKSI STROBERI (Fragaria Sp) DENGAN PEMBERIAN BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR (POC) SECARA HIDROPONIK SUBSTRAT. - Oktarina, Diana Okya; Armaini, Armaini; Ardian, Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Cultivation of Strawberries (Fragaria Sp) in substrates Hydroponics can use Liquid Organic Fertilizer (LOF) Super Bionics as a source of nutrients, which need to be investigated the accuracy of the concentration of application, with the aim of getting the best concentration for the growth and production of strawberris. Research was conducted experimentally using completely randomized design (CRD) with 6 treatments and 4 replicates ie liquid organic fertilizer Super Bionic with a concentration of 0 ml / l of water, 1.5 ml / l of water, 2 ml / l of water, 2.5 ml / l of water, 3 ml / l of water and 3.5 ml / l of water. Parameters observaced  such plant height (cm), number of leaves (leaf), days to flowering (days), the age of first harvest (days) and the weight of fruit  per plant (g). The results showed that the liquid organic fertilizer Super Bionic 3 ml / l of water provide the best results on all parameters observed such plant height, leaf number, date of flowering, the age of first harvest and  weight of fruit  per plant.    Keywords: Strawberries (Fragaria Sp), Super Bionic liquid organic fertilizer, substrates       hydroponics.